RIHLAH ILMIAH SEBAGAI WISATA INTELEKTUAL KAUM SANTRI - Umar Buchary Umar Buchary (Institut Agama Islam Negeri Madura)
Umar Buchary (Penulis, dosen STAIN Pamekasan, Jl. Raya Panglegur Km. 04 Pamekasan. dan mahasiswa Program Doktor Pascasarjana UIN Sunan Kalijaga Yogyakarta) Abstract Any activities that are aimed for any objectives to migrate from one place to other ones mean tourism.This article tends to criticize any romantical and semi-ceremonial interpretation of tourism. It offers tradition of rihlah ‘ilmiyyah that has been established in Pesantren since the 17th century. The aim is to develop and to comprehend Islamic science mastery of Santri (students studying in pondok pesantren) for the sake of Islamic scholarshipness they will experience in the future. Kata-kata kunci satri, pesantren dan rihlah ilmiah